CONCEPTUAL PROVISIONS OF HR STRATEGY IN THE CONTEXT OF DIGITALISATION - Криворучко, Оксана; Шморгун, Ольга (SWorldJournal, 2025)
The article develops conceptual provisions for the formation and implementation of an adaptive innovative human resource management strategy (AISHRM), which reflects a qualitatively new approach to HRM in the context of digital transformation of the econ